A Study on the Role of Pre-Gelatinized Starch (PGS) in the Non Damaging Drilling Fluid (NDDF) for the Tipam Sand of Geleki Oilfield of Upper Assam Basin - Talukdar, Prasenjit; Gogoi, Subrata Borgohain (International Journal of Applied Sciences and Biotechnology, 2015)
The drilling of the wells from surface to target location with conventional drilling fluids may impair production and ultimate recovery by failing to adequately connect the reservoir with the wellbore by damaging the producing interval. One of the most common ways of damaging a formation is the filtration loss. Non Damaging Drilling Fluid (NDDF) is a clay and barite free environmental friendly polymer mud system mostly used in pay zone sections of development wells and specifically in horizontal drilling to avoid formation damage. Starches [(C6H10O5) n] are an environment-friendly drilling mud additive for water-base drilling fluids used to control the filtration loss. This paper reports the effect and optimum composition of Pre-Gelatinized Starch (PGS) as a filtration control component in the NDDF. PGS is a high-quality nonionic polysaccharide having the Chemical Formula: C27H48O20 and Molecular Weight: 692.658020 [g/mol] which controls the filtration loss by sealing the walls of the borehole due to its long chains of monosaccharide. Some clay specifically the montmorillonite a member of the smectite group that generally also found in the payzones of Geleki Oilfield of Upper Assam Basin absorb hydrogen ions into their structure when comes in contact with fresh water and causing swelling of the clay resulting in a reduction of the pore volume and possibly plug in the pore throats. Therefore the filtration loss should be as low as possible by forming high quality low permeable mud cake of as thin as possible. In this work, an attempt has been made to study the effect of varying composition of PGS on the different mud properties of laboratory formulated NDDF and to choose its optimum composition based on the required mud parameters of the study area. Int J Appl Sci Biotechnol, Vol 3(2): 291-300 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12552